Pengaruh Rasio Keuangan dan Pertumbuhan Perusahaan terhadap Dividend Payout Ratio (DPR) dan Implikasinya pada Harga Saham Perusahaan Perbankan yang Listing di Bursa Efek Indonesia (BEI) - Megamawarni Megamawarni; Aliah Pratiwi (Jurnal Maksipreneur, 2021)
The rapid technological developments have an impact on the opening of global trade opportunities so that banks that carry out intermediary functions in the financial sector will be increasingly needed. The purpose of this study was to analyze the effect of financial ratio and company growth on the stock price of banks with the status of State-Owned Enterprises (SOE) listed on the Indonesia Stock Exchange (IDX) with Dividend Payout Ratio (DPR) as an intervening variable. This study is quantitative research with an associative approach. The research population includes 44 banking companies listed on the Indonesia Stock Exchange (IDX). The sample in this study amounted to four banks. The sampling technique used is purposive sampling. This study uses secondary data with data analysis methods used multiple linear regression analysis, partial test (t-test), and path analysis with the help of the SPSS version 23 application. This study indicates that DER significantly affects DPR, while ROE and company growth do not affect DPR. Furthermore, the DPR has a significant effect on stock prices, while DER and ROE have a significant effect on stock prices through the Dividend Payout Ratio (DPR), and company growth does not affect stock prices mediated by the Dividend Payout Ratio (DPR).